Using Asynchronous Discussion Forums to Enhance Engagement of Students in Online Teaching - Guanying Chu; Yu Wang; Qinglei Bu; Bing Han; Fei Xue; Enggee Lim (Acta Pedagogia Asiana, 2026)
The shift towards HyFlex learning in the post-pandemic era has introduced new challenges for higher education, particularly in maintaining student engagement and motivation in online learning environments. This paper examines the potential of anonymous asynchronous online discussion forums (AODFs) to enhance participation and engagement in large online classes. We propose a new model of forum management that integrates question-answering and peer-to-peer interaction, allowing students to post questions anonymously while responses remain non-anonymous. The study investigates the evolving roles of teachers and students in promoting and participating in forum activities, adopting a “students as partners” perspective. Data from the implemented AODF indicate increased student participation and motivation, with a substantial portion of non-academic questions addressed through peer discussion. Challenges such as lurking behavior and the limitations of relying solely on technology are also highlighted. The study underscores the critical role of instructors in evaluating and adapting emerging technologies to meet student needs and foster a sense of community in online learning environments.